2017
DOI: 10.3390/socsci6030104
|View full text |Cite
|
Sign up to set email alerts
|

Who Can I Turn To? Emotional Support Availability in African American Social Networks

Abstract: African Americans disproportionately experience psychological distress, such as feelings of sadness, hopelessness, and worthlessness and are disproportionately exposed to risk factors associated with mental illness, such as racial discrimination, violence and poverty. To effectively address African Americans' mental health needs, it is imperative to identify who African Americans turn to when they experience stressors. The purpose of this study was to assess the extent to which emotional support is provided wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Our findings revealed that respondents obtained appraisal of symptoms and emotional support from slightly more non-family members than family members. This is line with published evidence that show that peers are important for evaluating and guiding others with similar symptoms and providing emotional support 23 57…”
Section: Discussionsupporting
confidence: 89%
“…Our findings revealed that respondents obtained appraisal of symptoms and emotional support from slightly more non-family members than family members. This is line with published evidence that show that peers are important for evaluating and guiding others with similar symptoms and providing emotional support 23 57…”
Section: Discussionsupporting
confidence: 89%
“…Ensuring that quality information is offered in the context of averting stillbirth risk factors is key. One reason as to why emotional and information support was more prevalent could be that it is readily available unlike other forms of support such as material [ 41 ]. However, information support reduced slightly after experiencing a stillbirth most likely a reflection of a sense of loss and fear of causing more distress and stigma to the affected mother.…”
Section: Discussionmentioning
confidence: 99%